Cupressus torulosa-a Timber with a Bright Future - Mathauda, G. S. (Indian Forester, 1950)
cupressus torulosa is a fine timbel eminently suited for a number of specialized industries such as pencil making, battery separators and vats for storage of corrosive chemicals. The total requirements of these industries at a conservative estimate are 2Â½ lac cubic feet per annum. The tree can be propagated easily and with advantage on comparatively dry and hot slopes not well suited for carrying deodar. It is thus a timber with a bright future. Action should be taken to create large scale compact plantations capable of meeting the above requirements.